Yo-kai watch. 14 - Konishi, Noriyuki (VIZ Media, LLC, 2020)
"Nate and Hailey Anne can see what others cannot: Yo-kai of all shapes and forms! As the two befriend even more hilarious Yo-kai, it looks like Nate’s constant Yo-kai companion, Jibanyan, might be ready to rank up!"--Provided by publisher.